Sistem Informasi Digital Marketing Pemesanan Jasa Pembuatan Desain Video, Animasi dan Gambar - Rinaldy, Rinaldy; Alviansah, Irvan; Sumiati, Sumiati; Priyatna, Ade (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The current digital marketing system continues to advance, along with the development of increasingly sophisticated technology with the presence of the internet. Digital Marketing is the process of marketing a product or service through digital media or the internet that can reach wider consumers. This design creation service will be marketed via the internet or digital marketing so that its scope is even wider. And in a pandemic like this time it makes it easier to market without having direct contact with customers. Through digital marketing, it is hoped that it can make it easier for everyone who wants to buy video, animation and image design services without having to come far, even if there is an order from outside the city or even from abroad. Therefore the solution given is to build a Digital Marketing Information System for Making Video, Animation and Image Design Services. The method used in the design and software is the Waterfall method which uses several stages, namely planning, modeling, development and deployment. The web development framework uses the Codeigniter Formwork. It is hoped that the results of making digital web marketing can increase sales and make it easier for customers to find information